(untitled) (Agrikan Jurnal Agribisnis Perikanan, 2022)
Land quality determines and influences agricultural production, but long-term use of chemical fertilizers has degraded land quality. The use of organic fertilizers is a way out to improve soil fertility. Research with bokhasi organic fertilizer treatment of cow dung aims to see how much influence it has on changes in soil chemical properties. Sampling and soil analysis were carried out on soils treated with bokhasi cow dung organic fertilizer at doses of: no treatment (B0), 2 kg/plot (B1), 4 kg/plot (B2), 6 kg/plot (B3) and 8 kg/plot (B4). Soil samples were taken from each treatment and then analyzed based on soil chemical indicators, namely pH, C-Organic, N-Total, P-Total and available, K2O, basic cations, Cation Exchange Capacity and Base Saturation. The results showed that the application of organic fertilizers had no effect on changing the criteria for soil chemical properties for all treatments, namely pH was acidic, C-Organic and Total N had Low status, total P and available P had very high status, K2O had moderate status, Ca2+ moderate status, Mg2+ with high status, K+ and Na+ with low status, cation exchange capacity with medium status and Base Saturation with medium status. Correlation test on the application of organic fertilizer bokasi cow dung gave a positive relationship to pH, C-Organic, N-Total, Cation Exchange Capacity and Base Saturation, meaning that each increase in dose had a significant effect on changes and improvements in soil chemical properties, but available P gave negative relationship.